Ubiquitination and the proteasome rather than caspase‐3‐mediated C‐terminal cleavage are involved in the EAAT2 degradation by staurosporine‐induced cellular stress. Issue 4 (3rd December 2020) - Voss, Timo‐Daniel; Gerget, Maria; Linkus, Birgit; von Einem, Bjoern; Landwehrmeyer, G. Bernhard; Lewerenz, Jan
Abstract: Diminished glutamate (Glu) uptake via the excitatory amino acid transporter EAAT2, which normally accounts for 90% of total forebrain EAAT activity, may contribute to neurodegeneration via Glu‐mediated excitotoxicity. C‐terminal cleavage by caspase‐3 (C3) was reported to mediate EAAT2 inactivation and down‐regulation in the context of neurodegeneration. For a detailed analysis of C3‐dependent EAAT2 degradation, we employed A172 glioblastoma as well as hippocampal HT22 cells and murine astrocytes over‐expressing VSV‐G‐tagged EAAT2 constructs. C3 activation was induced by staurosporine (STR). In HT22 cells, STR‐induced C3 activation‐induced rapid EAAT2 protein degradation. The mutation of asparagine 504 to aspartate (D504N), which should inactivate the putative C3 cleavage site, increased EAAT2 activity in A172 cells. In contrast, the D504N mutation did not protect EAAT2 protein against STR‐induced degradation in HT22 cells, whereas inhibition of caspases, ubiquitination and the proteasome did. Similar results were obtained in astrocytes. Phylogenetic analysis showed that C‐terminal ubiquitin acceptor sites—but not the putative C3 cleavage site—exhibit a high degree of conservation. Moreover, C‐terminal truncation mimicking C3 cleavage increased rather than decreased EAAT2 activity and stability as well as protected EAAT2 against STR‐induced ubiquitination‐dependent degradation. We conclude that cellular stress associated with endogenous C3 activation degrades EAAT2 via a pathway involving ubiquitination and the proteasome but not direct C3‐mediated cleavage. In addition, C3 cleavage of EAAT2, described to occur in other models, is unlikely to inactivate EAAT2. However, mutation of the highly conserved D504 within the putative C3 cleavage site increases EAAT2 activity via an unknown mechanism. Abstract : Glutamate (Glu) released synaptically by neurons and extrasynaptically by the cystine (Cys)/Glu antiporter system xc‐ in astrocytes and microglia (µGlia) is rapidly taken up by the astrocytic glutamate transporter EAAT2. EAAT2 is prominently down‐regulated in neurodegenerative diseases, probably leading to overstimulation of glutamate receptors (GluR), neuronal calcium overload (Ca ++ ) and finally excitotoxicity. When recombinantly over‐expressed in neuroectodermal cells, EAAT2 is rapidly down‐regulated by staurosporine (STR)‐induced cellular stress associated with caspase 3 activation. We found that C‐terminal (COOH) caspase 3 cleavage does not play a role in this down‐regulation. Instead, C‐terminal lysines (Lys) are required for proteasomal degradation of EAAT2 following ubiquitination.